KEANEKARAGAMAN KUPU-KUPU DI KECAMATAN SUKARAME KOTA PALEMBANG PROVINSI SUMATERA SELATAN - Ririn Eka Putri (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2014)
The research about  diversity of buterflys  at Sukarame village was conducted March - April  2015. The objective of this research was collect buterflys. This research utilited the direct observation method during three week. This method used insecting nets. The result of the identification  geted 7 Order, 3 Family, 7 Genera, dan 10 Spesies. Key words : diversity, buterfly, Sukarame